2007
DOI: 10.1371/journal.pone.0000226
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 Modulates the Type 1 Immune Response

Abstract: Background/AbstractImmune responses initiated by T cell receptor (TCR) and costimulatory molecule mediated signaling culminate in maximal cytokine mRNA production and stability. The transcriptional responses to co-stimulatory T cell signalling involve calcineurin and NF-AT, which can be antagonized by interference with the cis-trans peptidyl-prolyl isomerases (PPIase), cyclophilin A and FKBP. Signalling molecules downstream of CD28 which are essential for the stabilization of cytokine mRNAs are largely unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…2C). These results were consistent with the previous reports showing Pin1 inhibition selectively suppressed IFN-␥ expression in bronchoalveolar lavage cells (23,24). We then established Pin1-overexpressing human primary chondrocytes using ankle tissues obtained during surgery in an osteoarthritic patient.…”
Section: Role Of Pin1 In Proinflammatory Protein Expressionsupporting
confidence: 92%
See 1 more Smart Citation
“…2C). These results were consistent with the previous reports showing Pin1 inhibition selectively suppressed IFN-␥ expression in bronchoalveolar lavage cells (23,24). We then established Pin1-overexpressing human primary chondrocytes using ankle tissues obtained during surgery in an osteoarthritic patient.…”
Section: Role Of Pin1 In Proinflammatory Protein Expressionsupporting
confidence: 92%
“…2C). It has been shown that Pin1 knockout mice show both Th1 and Th2 abnormalities (23). Hence, we additionally determined the mRNA expression of IFN-␥ (Th1 dependent) and IL-4 production (Th2 dependent) in both GFP-HTB94 and Pin1-HTB94 cells.…”
Section: Role Of Pin1 In Proinflammatory Protein Expressionmentioning
confidence: 99%
“…cently, we showed significantly reduced collagen deposition in the airways or plura of Pin1 null rodents after the induction of allergic asthma or MHC-mismatched lung transplantation, respectively (9,10). Therefore, we assessed if Pin1 was also important for interstitial fibrosis and thus assessed the effects of BLM, which models many features found in human IPF (15).…”
Section: Pin1 Is Required For Blm-induced Collagen Deposition-re-mentioning
confidence: 99%
“…The altered expression of MMPs and TIMPs suggests an involvement of Pin1 in TGF-␤1 signaling and Fb gene regulation (10). Because resident Fb account for 30% of total lung cells and are the main producer of ECM (22), we established primary lung Fb cultures from wildtype and Pin1 Ϫ/Ϫ mice.…”
Section: Blm or Saline Control Was Introduced Intratracheally (2) Intmentioning
confidence: 99%
See 1 more Smart Citation